REVIEW OF THE MEETINGS OF THE UNITED NATIONS OPEN WORKING GROUP ON CYBERSECURITY WITH THE WAR IN UKRAINE AS A BACKGROUND IN 2023 (Вісник: Міжнародні відносини, 2025)
Background. The fourth and fifth meetings of the United Nations Open Working Group addressed issues of cybersecurity policy. The process of developing legal mechanisms was complicated by politicized discussions, with Russia participating with its geopolitical interests in mind against the backdrop of the ongoing war in Ukraine.Methods. The study employed methods such as the analysis of materials, publications, and analytical reports, an interdisciplinary approach (analyzing international law, diplomatic documents, technical aspects of cyber defense, and the geopolitical context), comparative analysis, content analysis of texts, and the use of secondary sources (scientific articles and analytical reports).Results. The outcomes of the mentioned meetings were reviewed, emphasizing the geopolitical context of the discussions and providing forecasts regarding the development of cybersecurity policy.Conclusions. The main problematic points in the discussions among different delegations during the Working Group meetings were considered. Both Russia's geopolitical interests regarding cybersecurity policy and some interests of other countries were highlighted. The discussion of cybersecurity issues was linked to problems of political sovereignty and the principle of non-interference, which are important classical issues in international relations. As a conclusion, the necessity of further development of legal norms and mechanisms regulating cybersecurity was postulated.